THE RELATIONSHIP AMONG TRANSFORMATIONAL LEADERSHIP AND PRINCIPAL INTERPERSONAL COMMUNICATION WITH THE WORK EFFECTIVENESS OF PUBLIC JUNIOR HIGH SCHOOL TEACHERS IN TANJUNG REDEB - ahmadong ahmadong ahmadong (Universitas Muhammadiyah Lampung, 2022)
This research is to analyze the relationships among transformational leadership and headmaster interpersonal communication with teachers work effectiviness. This research is conducted at public junior high schools (SMPN) in Tanjung Redeb Distric, Berau Regency. This research takes the samples randomly, 108 teachers of 147 population. This research result indicates that there are positive correlations between (I) headmaster leadership transformational (X1) with teachers work effectiviness (Y) with correlations coefficient r= ,722 at the level at significance (α= ,05); (2) headmaster interpersonal communication (X2) and teachers work effectiviness (Y) with correlations coefficient r= ,710 at the level at significance (α= ,05); (3) a positive correlation between headmaster leadership transformational (X1) and interpersonal communication (X2) with teachers work effectiviness (Y) with correlation coefficient r= ,766 at the significance level (α=,05).